Representation of Cosmological Values in the Architecture of Traditional Toba Batak Houses - Tifany; Situmorang, Rahel Theresia Rodame; Silaban, Immanuel; Siregar, Arjuna Junifer; Siberani, Robert (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
The architecture of Toba Batak traditional houses is a cultural heritage of the Indonesian archipelago, rich in symbolism and cosmological values. This study aims to examine the representation of cosmological values in the structure, spatial layout, and ornamentation of Toba Batak traditional houses, and to understand how these values function in the socio-cultural life of the community. Using a descriptive qualitative method with an anthropolinguistic approach and symbolic analysis, data were collected through literature review. The results show that Toba Batak traditional house architecture functions not only as a residence but also as a manifestation of the cosmos, composed of three main layers: the upper world (banua ginjang), the middle world (banua tonga), and the lower world (banua toru). This spatial division is represented through the stilt structure of the house, the orientation of the building facing north or the rising sun, and the use of gorga ornaments, which symbolize life, strength, and protection. Furthermore, the house’s raised-from-the-ground construction system reflects the concept of separating sacred and profane space, while the curved roof symbolizes the human connection with ancestors and divine powers. This research confirms that Toba Batak architecture is a medium for transmitting cosmological values that continue to live on in the community’s cultural practices. These findings are expected to contribute to the preservation of traditional architecture and the development of vernacular architectural studies in Indonesia.